2019
DOI: 10.1002/wer.1193
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of surfactant using dolochar: A kinetic and statistical modeling approach

Abstract: Disturbingly high rates of consumption of surfactants in household and industries have led to mark them as emerging contaminants in the environment. In the present work, removal of sodium dodecyl sulfate (SDS), an anionic surfactant, using an industrial waste (dolochar) was explored. The adsorbent material was characterized with the help of Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Kinetic evaluation was performed using first, pseudo-first, second, and pseudo-second order mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…After this time, the adsorption density smoothes, indicating a gradual adsorption. Shami et al (2020) observed a similar effect on the adsorption of surfactant sodium dodecyl sulfate on dolochar, and observed that these two steps represent that boundary layer diffusion can be considered the rate-limiting step in the initial adsorption phase and intraparticle diffusion is the rate limiting step in the final step. Although the models indicate a lower adsorption capacity in equilibrium for the temperature of 45 °C, the constants K1 and K2 are higher for this temperature, which represents a fast adsorption in the initial moments of contact between the adsorbent and the adsorbate, indicating high mass transfer rate.…”
Section: Adsorption Kineticsmentioning
confidence: 72%
“…After this time, the adsorption density smoothes, indicating a gradual adsorption. Shami et al (2020) observed a similar effect on the adsorption of surfactant sodium dodecyl sulfate on dolochar, and observed that these two steps represent that boundary layer diffusion can be considered the rate-limiting step in the initial adsorption phase and intraparticle diffusion is the rate limiting step in the final step. Although the models indicate a lower adsorption capacity in equilibrium for the temperature of 45 °C, the constants K1 and K2 are higher for this temperature, which represents a fast adsorption in the initial moments of contact between the adsorbent and the adsorbate, indicating high mass transfer rate.…”
Section: Adsorption Kineticsmentioning
confidence: 72%
“…Berbagai proses pengolahan atau pemisahan surfaktan dalam limbah telah dilakukan, diantaranya dengan adsorpsi menggunakan berbagai adsorben seperti bahan komposit MCM-41 (Ariapad, 2012), karbon aktif (Bindes, 2015), adsorben dolochar (Shami, 2019), menggunakan proses oksidasi O3/UV/H2O2 (Arslan, 2017), menggunakan metode gabungan koagulasi/flokulasi/sedimentasi dengan membran (Nascimento, 2019) dan menggunakan reaktor membran aerobik termofilik (Collivignarelli, 2019). Pada penelitian ini digunakan metode elektrokoagulasi pada proses pengolahan limbah simulasi surfaktan yang dilanjutkan dengan pengukuran kadar surfaktan secara spektroforometer.…”
Section: Pendahuluanunclassified